Probability, random variables, and random signal principles - Peyton Z. Peebles, Jr. (McGraw-Hill, 2021)
The fourth edition of "Probability, Random Variables and Random Signal Principles" continues the success of previous editions with its concise introduction to probability theory for the junior-senior level course in electrical engineering. The book offers a careful, logical organization which stresses fundamentals and includes almost 900 student exercises and abundant practical applications for engineers to understand probability concepts. The most important new material in this edition relates to discrete-time random processes and sequences, and other topics in the general area of digital signal processing, such as the DT linear system.